2011
DOI: 10.1080/01496395.2010.534121
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Study of the Synthesis of 1,1-Dibutoxyethane in a Fixed-Bed Adsorptive Reactor

Abstract: To link to this Article: DOI: 10.1080/01496395.2010.53412

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…The high value obtained for the correlation coefficient computed using Eq. (19), 0.987, allowed to confirm that the mathematical model implemented was able to accurately describe the breakthrough curves for all species, considering the estimated adsorption parameters.…”
Section: Adsorption Equilibrium Isothermsmentioning
confidence: 90%
See 4 more Smart Citations
“…The high value obtained for the correlation coefficient computed using Eq. (19), 0.987, allowed to confirm that the mathematical model implemented was able to accurately describe the breakthrough curves for all species, considering the estimated adsorption parameters.…”
Section: Adsorption Equilibrium Isothermsmentioning
confidence: 90%
“…However, more recent studies demonstrated that this model is not able to predict the multicomponent adsorption equilibrium over resins with high cross-link degrees that contain highly polar functional groups [41,47,48]. On the other hand, for the particular case of reactiveadsorptive processes comprising acetalization reactions, the Langmuir model has been indicated as an interesting alternative [17][18][19][20], since it does not require extensive computation and it has demonstrated to be able to predict the experimental data reported with significant accuracy. Eq.…”
Section: Property Valuementioning
confidence: 90%
See 3 more Smart Citations